MEKANISME PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN SUPERVISI TERHADAP KINERJA GURU: PERAN MODERASI STATUS SEKOLAH DI KECAMATAN SERANG - Cahyaningtyas, Ovi Sakti; Muhammad Suparmoko; Budi Ilham Maliki (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study examined the influence of school principal leadership, supervision, and school status on teacher performance among 176 elementary school teachers in Serang District. Using Partial Least Squares Structural Equation Modeling (PLS-SEM), the study found that the three latent variables significantly explained [percentage]% of the variance in teacher performance (p < 0.05). Path coefficients indicated that school principal leadership had the strongest direct and indirect influence on teacher performance, followed by supervision and school status. These findings support the transformational leadership theory and are consistent with previous research. The results also have important implications for educational policy. Improving the quality of school principal leadership, strengthening supervision systems, and enhancing school status are strategic steps to improve teacher performance and, ultimately, overall educational quality.